Estudio de factibilidad para la creación de un taller de mecánica agro industrial en la ciudad de Quevedo periodo 2011 - 2015. - Perez Quinto, Elizabeth Herlinda (2012)
This research work studies the feasibility of an agro-industrial machine workshop, considering the strength of Quevedo city and nearby towns such as Valencia, San Carlos, Buena Fe and Mocache in the agricultural, and the importance in recent years are taking the use of agro-industrial machines in the process of agricultural production, leaving the notion that only large farmers must invest in machinery, however currently are considering this type of investment as an option to optimize available resources and reduce spending on wages. The market study found that farmers in this area have a great interest in the use of harvesters and dryers, so often rent these machines, more for lack of knowledge where can buy them and the prices, if they had access to more information they can invest in order to increase profitability. There are a limited number of agribusiness mechanical workshops in the area of Quevedo and surroundings, most of them small and medium businesses manage by their owners, but do not maintain exclusivity within the same type of machinery, offering a wide range, and this factor which allows they to have experience in all, but no specialty. The economic study details the initial investment, which amounts to $ 46,656.44, which will be financed by 30% equity and 70% for bank loans. The financial study established the value of VAN at $153,157.51, TIR at 92.43% and the benefit - cost ratio at 1.33, so this project is considered executable. The environmental impact analysis provided a project indicates how to decrease the environmental impact of an agribusiness machine shop, because this type of business is located in category "B".